Political parties in the eighties - Goldwin, Robert A.; American Enterprise Institute for Public Policy Research; Public Affairs Conference Center (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1980)
"Most of the essays in this volume were originally presented at a joint conference of the American Enterprise Institute and the Public Affairs Conference Center of Kenyon College."
Includes bibliographical references.
osa 22/01/19
Loans
Keywords: Political parties